Maternal adherence to micronutrient supplementation before and during pregnancy in Northwest China: a large-scale population-based cross-sectional survey. Issue 8 (8th August 2019) - Liu, Danmeng; Cheng, Yue; Dang, Shaonong; Wang, Duolao; Zhao, Yaling; Li, Chao; Li, Shanshan; Lei, Fangliang; Qu, Pengfei; Mi, Baibing; Zhang, Ruo; Li, Jiamei; et al.
Abstract : Objectives: To report the situation of maternal micronutrient supplementation before and during pregnancy in Northwest China and to examine the rates of and factors related to the adherence to micronutrient supplementation among pregnant women in this region, where dietary micronutrient intake is commonly insufficient. Design: A large-scale population-based cross-sectional survey. Setting: Twenty counties and ten districts of Shaanxi Province. Participants: A sample of 30 027 women were selected using a stratified multistage random sampling method. A total of 28 678 women were chosen for the final analysis after excluding those who did not provide clear information about nutritional supplementation before and during pregnancy. Main outcome measures: Maternal adherence to micronutrient supplementation (high and low) were the outcomes. They were determined by the start time and duration of use according to Chinese guidelines (for folic acid (FA) supplements) and WHO recommendations (for iron, calcium and multiple-micronutrient (MMN) supplements). Results: In total, 83.9% of women took at least one kind of micronutrient supplement before or during pregnancy. FA (67.6%) and calcium (57.5%) were the primarily used micronutrient supplements; few participants used MMN (14.0%) or iron (5.4%). Adherence to supplementation of all micronutrients was low (7.4% for FA, 0.6% for iron, 11.7% for calcium and 2.7% for MMN). Higher educational levels, higher income levels, urban residence and better antenatal care (including pregnancy consultation and a higher frequency of antenatal visits) were associated with high adherence to micronutrient supplementation. Conclusion: Maternal micronutrient supplementation before and during pregnancy in Northwest China was way below standards recommended by the Chinese guidelines or WHO. Targeted health education and future nutritional guidelines are suggested to improve this situation, especially in pregnant women with disadvantaged sociodemographic conditions.